DOI: 10.11606/d.47.2018.tde-24092018-112047
|View full text |Cite
|
Sign up to set email alerts
|

Compreendo a experiência emocional da maternidade em mães de bebês com deficiência

Abstract: History shows that, in ancient times, people with disabilities were sacrificed or delivered to care entities and, even creating the idea of maternal love and family's understanding as the main institution to take responsibility for childcare, it was necessary much time for the child with disabilities to become part of their family. Psychoanalysis contributed to the contemporary conception of the importance of the mother's role. Thus, to understand the development of the subject, it is necessary to look at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Encontramos, também, pesquisas qualitativas interessantes em psicologia, como a de Lima (2012) que utilizou como metodologia a clínicaqualitativa com a aplicação das pranchas do TAT; os estudos sobre os papeis sociais de Silva (2012); pesquisas com foco na mortalidade infantil, como a de Lima ( 2010); e a relação de mulheres com o mercado de trabalho, de Lopes et al (2014). A pesquisa que mais nos interessou, ou se aproximou do nosso olhar sobre o tema, foi a dissertação de Carvalho (2015), que fez um estudo de caso com base em depoimentos de mulheres que tiveram seu primeiro filho após os 35 anos, com foco nos impactos da maternidade avançada e sua contribuição na identidade feminina.…”
Section: Dos "Ditos" Acadêmicosunclassified
“…Encontramos, também, pesquisas qualitativas interessantes em psicologia, como a de Lima (2012) que utilizou como metodologia a clínicaqualitativa com a aplicação das pranchas do TAT; os estudos sobre os papeis sociais de Silva (2012); pesquisas com foco na mortalidade infantil, como a de Lima ( 2010); e a relação de mulheres com o mercado de trabalho, de Lopes et al (2014). A pesquisa que mais nos interessou, ou se aproximou do nosso olhar sobre o tema, foi a dissertação de Carvalho (2015), que fez um estudo de caso com base em depoimentos de mulheres que tiveram seu primeiro filho após os 35 anos, com foco nos impactos da maternidade avançada e sua contribuição na identidade feminina.…”
Section: Dos "Ditos" Acadêmicosunclassified
“…Also in Brazil, three studies have reported heteronormative barriers, both in the imaginations of health professionals who stipulate that biological reproduction is impossible for these couples, disregarding other alternative means of forming a family 13 , and in the configuration of reproduction clinics designed for heterosexual families, whose environments feature only photographs of cisgender couples of men and women 34 . Some lesbian couples could not participate in choosing the assisted reproduction technology and reported a lack of information, a lack of receptiveness in response to their anguish and, at times, dubious looks, although they considered the process as a whole in a positive light, either because they underwent the procedure and valued the experience of motherhood more than the difficulties of the process or also because the clinic did not deny care in view of their sexuality at variance with the hegemonic norm 37 . There were also situations where clinics denied care, explaining that it was because the family formation differed from the standard served by the service 34 .…”
Section: Barriers To Reproduction and Reproductive Health Of Cis Same...mentioning
confidence: 99%
“…Alguns casais de lésbicas não puderam participar da escolha da técnica de reprodução assistida e relataram falta de informação, de acolhimento diante de suas angústias e, em alguns momentos, a presença de olhares de desconfiança, embora a compreensão do processo como um todo tenha sido positiva. Seja porque passaram pelo procedimento e valorizam a experiência da maternidade mais do que as dificuldades do processo, ou porque a clínica não negou atendimento diante de sua sexualidade diferente da hegemônica 37 . Também houve situações em que o atendimento na clínica foi negado, sendo explicitado que o motivo era por ser uma constituição familiar divergente do padrão atendido pelo serviço 34 .…”
Section: Barreiras à Reprodução E à Saúde Reprodutiva De Casais Homop...unclassified